Autonomous Sensor System for Low-Capacity Wind Turbine Blade Vibration Measurement - Diego Muxica; Sebastian Rivera; Marcos E. Orchard; Constanza Ahumada; Francisco Jaramillo; Felipe Bravo; José M. Gutiérrez; Rodrigo Astroza (Sensors, 2024)
This paper presents the design, implementation, and validation of an on-blade sensor system for remote vibration measurement for low-capacity wind turbines. The autonomous sensor system was deployed on three wind turbines, with one of them operating in harsh weather conditions in the far south of Chile. The system recorded the acceleration response of the blades in the flapwise and edgewise directions, data that could be used for extracting the dynamic characteristics of the blades, information useful for damage diagnosis and prognosis. The proposed sensor system demonstrated reliable data acquisition and transmission from wind turbines in remote locations, proving the ability to create a fully autonomous system capable of recording data for monitoring and evaluating the state of health of wind turbine blades for extended periods without human intervention. The data collected by the sensor system presented in this study can serve as a foundation for developing vibration-based strategies for real-time structural health monitoring.